(3JMQjQ GdNUGUI aj JjSjQ GdNdGUIs - (3YeQ Hf eXaQ Hf YeQ H eMeO GHf CHj GdahGQS, CHh MaU, Rjf GdOjf GHf GdhQOj GdeYQj GdcfOj,J (B749 (3g` s; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3Ydj Hf CMeO Hf Ydj Hf YeQ Hf CMeO Hf CHj HcQ Hf SGde Gdjefj Gdecj GdTgjQ HGdShGHWj s)
(3ChdgG (B:s
(3CeG HYO, aEfj QCjJ cJGH GdNdGUI GdCdajI aj Yde GdYQHjI ddEeGe GdeTMhfI HGdahGFO s
(3BNQgG (B:s
(3eKd hef jTGb Gddg, hCaYd aj GdJYLH cCMHH Hg ceG GdJRe GdEOZGe aj gde, ade jbd gdee BNQ GdcJGH s
(3fKQ ajg GdeDda NdGUI CdajI GHf eGdc aj GdfMhs
(3egedI GdfbW CMjGfkGs
(3HChdgG Jedc eDQN aj (B969(3g```s
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdfMhs